2003
DOI: 10.1093/tropej/49.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hospital Stay on Nutritional Anthropometric Data in Turkish Children

Abstract: We evaluated the effects of hospital stay on nutritional anthropometric data in children of various age groups and investigated the effects of admission undernutrition on nutritional anthropometric data in children who were hospitalized in our university hospital in Turkey. The adverse effect of hospitalization on nutritional status was shown to be most obvious on the 2-6-year age group with undernourished children. We also found reduced anthropometric parameters in all patients with mild malnutrition at admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 0 publications
2
22
1
7
Order By: Relevance
“…Our study indicates that the fact that families present due to retarded growth does not necessarily mean that we will encounter higher retarded growth levels than might be expected from the literature. Öztürk et al determined nutritional deficiency in 31.8% of children presenting to hospital at any time (12). The incidence of malnutrition in international studies of children presenting to hospital is 20.4% in Brazil (452 surgical patients were enrolled), 18.7% in Australia (203 surgical patients enrolled), 27% in Colombia (174 surgical and non-surgical patients enrolled) and 4.5% in New Zealand (157 non-surgical patients enrolled) (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that the fact that families present due to retarded growth does not necessarily mean that we will encounter higher retarded growth levels than might be expected from the literature. Öztürk et al determined nutritional deficiency in 31.8% of children presenting to hospital at any time (12). The incidence of malnutrition in international studies of children presenting to hospital is 20.4% in Brazil (452 surgical patients were enrolled), 18.7% in Australia (203 surgical patients enrolled), 27% in Colombia (174 surgical and non-surgical patients enrolled) and 4.5% in New Zealand (157 non-surgical patients enrolled) (13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…A past study conducted with hospitalised pediatric patients emphasised that undernutrition on admission in children remains unrecognised by our healthcare workers, malnourished children are still not recognised sufficiently by pediatricians and that specific nutritional support is not used systematically (28). Especially, pediatric patients with mild malnutrition on admission were considered to be at the highest risk of adverse effect of hospitalisation and thus, this population of patients was recommended to be given special attention (28).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, pediatric patients with mild malnutrition on admission were considered to be at the highest risk of adverse effect of hospitalisation and thus, this population of patients was recommended to be given special attention (28). Therefore, future efforts in pediatric nutrition should include identifying those patients who require nutritional support, ensuring the provision of appropriate nutritional management and educating hospital staff about the identification and management of malnutrition (16).…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study found that minors with malnutrition on admission had lost more BMI on discharge than those with better nutritional status on admission [18]. On the other hand, a Turkish study found that hospital stay had a negative impact on the nutritional status of children with mild malnutrition on admission but not of children with moderate malnutrition on admission [17]. Normal weight and mildly malnourished patients do not draw the attention of the health care team to a possible need of nutritional support, while patients with moderate malnutrition receive special care.…”
Section: Hospital Malnutrition: Associated Factorsmentioning
confidence: 99%
“…Despite all the scientific knowledge, the prevalence of malnutrition in the last 10 years has not decreased [14]. In countries like Brazil and Turkey, for instance, the prevalence of acute hospital malnutrition on admission reach alarming figures, ranging from 33.8% to 52.4% [15][16][17]. Most of the studies use Body Mass Index (BMI) or weight for height greater than two Standard Deviations (SD) to define acute malnutrition and height for age greater than less DP to determine chronic malnutrition [2].…”
Section: Introductionmentioning
confidence: 99%